If x(2−√2)=y(2+√2)=1x(2−√2)=y(2+√2)=1x(2−√2)=y(2+√2)=1, find the value of x2−y2x2−y2x2−y2.
Answer:
2√22√22√2
- Since x(2−√2)=1x(2−√2)=1x(2−√2)=1, we can say that x=12−√2x=12−√2x=12−√2.
- Now if we multiply both numerator and denominator of the given fraction by 2+√22+√22+√2, we get:
12−√2×2+√22+√212−√2×2+√22+√212−√2×2+√22+√2
[Math Processing Error] - From above steps we get x=2+√22x=2+√22.
- Similarly, for y(2+√2)=1y(2+√2)=1, we can say that:
y=12+√2y=12+√2. - Now if we multiply both numerator and denominator by 2−√22−√2, we get:
12+√2×2−√22−√212+√2×2−√22−√2
[Math Processing Error] - From the step 44 and 55, we get: y=2−√22y=2−√22.
- [Math Processing Error]